Tambor de crioula: desde o ventre das minhas ancestrais - Morais, Cleuma Alexsandra Sousa (2023)
The main theme of this work is the cultural manifestation of the Creole drum, presenting a look at the historical perspective of the Creole drum and its relationship with ancestry, with this manifestation being used as a creative element to think about a re-elaboration of this tradition of origin in society. contemporary, based on elements of the dance itself, as well as the relationship between the performer's body and her ancestries, in line with the methodological assumptions presented by professor Drª Inaicyra Falcão (2019). The research proposes to think about a creative process in dance that walks through crossroads (Rufino, 2016), in encounters between popular knowledge and practices with different perspectives for the creation of new possible paths. The research leads to a creative process that has its analyzes based on some of the seven African dance principles studied by professor Drª Maria de Lourdes Barros da Paixão (2009), namely: holistic sense, cyclical and circular form; polycentrism; dimensionality; imitation and harmony and repetition.